1998
DOI: 10.1046/j.1440-1703.1998.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of flowering on bird community dynamics in some central Victorian eucalypt forests

Abstract: Many species of Eucalyptus in Australia provide copious amounts of nectar during their reproductive seasons. The nectar is used by many animal species but especially by birds, insects and some bats, which act as pollinators. One of the major features of eucalypt flowering in southern Australia is the patchy, asynchronous flowering of different species, which appears to drive mass nomadism of nectarivorous birds among regions and among habitats. Here we explore whether flowering asynchrony or climate is primari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 56 publications
2
43
0
Order By: Relevance
“…Thus, most honeyeaters are highly mobile generalist foragers well adapted to the heterogeneous flowering landscape over which nectar is produced (Ford et al, 1979;McGoldrick and MacNally, 1998). In our study, this was demonstrated by 77% of all within-population bird movements being beyond nearest neighbours, and 68% of observed movements leaving the local population.…”
Section: Pollen Vectorsmentioning
confidence: 51%
See 2 more Smart Citations
“…Thus, most honeyeaters are highly mobile generalist foragers well adapted to the heterogeneous flowering landscape over which nectar is produced (Ford et al, 1979;McGoldrick and MacNally, 1998). In our study, this was demonstrated by 77% of all within-population bird movements being beyond nearest neighbours, and 68% of observed movements leaving the local population.…”
Section: Pollen Vectorsmentioning
confidence: 51%
“…Consequences of pollination by nectar-feeding honeyeaters A major feature of bird-pollinated plants in temperate southern Australia is a patchy, asynchronous flowering of different species, which is a principal driver of mass nomadism of nectarivorous birds among regions and habitats (McGoldrick and MacNally, 1998). Thus, most honeyeaters are highly mobile generalist foragers well adapted to the heterogeneous flowering landscape over which nectar is produced (Ford et al, 1979;McGoldrick and MacNally, 1998).…”
Section: Pollen Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data are from six major survey programmes (Table 1). In each programme, ‡ 2 survey rounds were conducted in both the 'cooler' (May-September) and the warmer (October-April) parts of the year to capture seasonal variation in the avifaunas (McGoldrick & Mac Nally, 1998). The regional-scale sites were surveyed between 1995 and 1997.…”
Section: Sources Of Bird Occurrence Datamentioning
confidence: 99%
“…For these species, a reserve system must not only provide breeding and wintering areas (often widely separated), but there must be continuity of habitat between reserves. For food nomads the requirements are more complex as required food resources shift in space and time with changing weather patterns, season, and from year to year (Collins and Newland 1986;Ramsey 1989;Mac Nally and McGoldrick 1997;McGoldrick and Mac Nally 1998).…”
Section: Conservation and Managementmentioning
confidence: 99%